FAKTOR PEMBENTUK PRODUCT ATTITUDE SERTA DAMPAKNYA TERHADAP PURCHASE INTENTION: PENELITIAN PADA MINAT BELI UPCYCLED PRODUCT - Fachry Ali Muzakki; Whony Rofianto (Journal of Accounting, Management and Islamic Economics, 2023)
The increase in population is the main factor in increasing the amount of waste. This condition, if there is no effort to handle good waste management, will cause environmental pollution. The emergence of the waste problem in DKI Jakarta is thought to be inseparable from various factors, including a lack of knowledge about the environment and low social factors.This study used a descriptive research design approach with empirical data collected through a sample online survey of millennials in Jabodetabek. The empirical data is then processed using the Structural Equation Modeling approach to test a number of proposed hypotheses. The results of the conclusions of this study are as follows: Green Value has a significant positive effect on Product Attitude,Functional Value has a significant influence on Product Attitude, Emotional Value has a significant positive effect on Product Attitude, Aesthetic Value has a significant positive effect on Product Attitude.Social Value has a significant positive effect on Product Attitude,Self Expressive Value has a significant positive effect on Product Attitude,Product Attitude has a significant positive effect on Purchase Intention.